Mass screening strategy for the SARS-CoV-2 Delta variant outbreak in Guangzhou, May 2021. (July 2022) - Zhang, Chao; Liang, Bingshao; Xiong, Zhile; Liang, Zhuwei; Gong, Sitang; Zhou, Zhenwen
Graphical abstract: Image 1